The Tomato MIXTA-Like Transcription Factor Coordinates Fruit Epidermis Conical Cell Development and Cuticular Lipid Biosynthesis and Assembly. Issue 4 (6th October 2015) - Lashbrooke, Justin; Adato, Avital; Lotan, Orfa; Alkan, Noam; Tsimbalist, Tatiana; Rechav, Katya; Fernandez-Moreno, Josefina-Patricia; Widemann, Emilie; Grausem, Bernard; Pinot, Franck; Granell, Antonio; Costa, Fabrizio; et al.
Abstract : A MIXTA-like transcription factor from tomato regulates fruit cutin biosynthesis, and is part of a regulatory network linking epidermal cell development with cuticle formation. Abstract: The epidermis of aerial plant organs is the primary source of building blocks forming the outer surface cuticular layer. To examine the relationship between epidermal cell development and cuticle assembly in the context of fruit surface, we investigated the tomato ( Solanum lycopersicum ) MIXTA-like gene. MIXTA/MIXTA-like proteins, initially described in snapdragon ( Antirrhinum majus ) petals, are known regulators of epidermal cell differentiation. Fruit of transgenically silenced SlMIXTA-like tomato plants displayed defects in patterning of conical epidermal cells. They also showed altered postharvest water loss and resistance to pathogens. Transcriptome and cuticular lipids profiling coupled with comprehensive microscopy revealed significant modifications to cuticle assembly and suggested SlMIXTA-like to regulate cutin biosynthesis. Candidate genes likely acting downstream of SlMIXTA-like included cytochrome P450s (CYPs) of the CYP77A and CYP86A subfamilies, LONG-CHAIN ACYL-COA SYNTHETASE2, GLYCEROL-3-PHOSPHATE SN-2-ACYLTRANSFERASE4, and the ATP-BINDING CASSETTE11 cuticular lipids transporter. As part of a larger regulatory network of epidermal cell patterning and L1-layer identity, we found that SlMIXTA-like acts downstream of SlSHINE3 and possibly cooperates with homeodomain Leu zipper IV transcription factors. Hence, SlMIXTA-like is a positive regulator of both cuticle and conical epidermal cell formation in tomato fruit, acting as a mediator of the tight association between fruit cutin polymer formation, cuticle assembly, and epidermal cell patterning.